2023
DOI: 10.1021/acs.analchem.3c03135
|View full text |Cite
|
Sign up to set email alerts
|

N-(4-Aminobutyl)-N-ethylisopropanol and Co2+ Dual-Functionalized Core–Shell Fe3O4@Au/Ag Magnetic Nanomaterials with Strong and Stable Chemiluminescence for a Label-Free Exosome Immunosensor

Manli Wang,
Jiangnan Shu,
Shanshan Wang
et al.

Abstract: Recently, magnetic beads (MBs) are moving toward chemiluminescence (CL) functional magnetic nanomaterials with a great potential for constructing label-free immunosensors. However, most of the CL-functionalized MBs suffer from scarce binding sites, easy aggregation, and leakage of CL reagents, which will ultimately affect the analytical performance of immunosensors. Herein, by using core–shell Fe3O4@Au/Ag magnetic nanomaterials as a nanoplatform, a novel N-(4-aminobutyl)-N-ethylisopropanol (ABEI) and Co2+ dua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…As shown in Figure A, the green curve showed that NiCo-DH-AA exhibited a significant CL emission. Compared to the ABEI and Co 2+ -functionalized nanomaterials previously reported by our group, the CL intensity of NiCo-DH-AA was 130 times higher than that of MB@ABEI-Au/Co 2+ (MAA/Co 2+ ) (black curve), 19 times higher than that of dfCL-MB(red curve), and 3 times higher than that of Fe 3 O 4 @Au/Ag/ABEI/Co 2+ (blue curve) . To clarify the origin of the superior CL emission of NiCo-DH-AA, a series of control experiments were carried out.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Figure A, the green curve showed that NiCo-DH-AA exhibited a significant CL emission. Compared to the ABEI and Co 2+ -functionalized nanomaterials previously reported by our group, the CL intensity of NiCo-DH-AA was 130 times higher than that of MB@ABEI-Au/Co 2+ (MAA/Co 2+ ) (black curve), 19 times higher than that of dfCL-MB(red curve), and 3 times higher than that of Fe 3 O 4 @Au/Ag/ABEI/Co 2+ (blue curve) . To clarify the origin of the superior CL emission of NiCo-DH-AA, a series of control experiments were carried out.…”
Section: Results and Discussionmentioning
confidence: 99%
“…CL-functionalized nanomaterials with good biocompatibility and high CL emission have been widely used as analytical nanoprobes. To date, various types of CL-functionalized nanomaterials have been synthesized, including metal nanoparticles, metal nanoclusters, carbon nanomaterials, metal–organic frameworks, magnetic nanomaterials, and hydrogels. Depending on whether these nanomaterials can catalyze the CL reaction or not, these CL-functionalized nanomaterials can be classified into two categories. The first category of CL-functionalized nanomaterials is using nanomaterials without CL catalytic activity as carriers, such as polydopamine, Fe 3 O 4 magnetic beads, silicon dioxide, and covalent organic frameworks .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Various analytical methods have been developed to overcome these limitations, including fluorescence, 23–25 electrochemical, 26,27 surface-enhanced Raman spectroscopy (SERS), 28,29 electrochemiluminescence, 30–32 chemiluminescence, 33 photoelectrochemical biosensing assays (PEC), 34,35 and colorimetric assays. 36,37 These methods not only enhance the sensitivity of DNMT detection, are easy to operate, and are low cost, but also provide certain advantages in the detection of other molecular biomarkers in the biological field, such as exosomes, 38–40 nucleic acids, 41–43 proteins, 44,45 antibodies, 46,47 cells, 48,49 enzymes, 50,51 and other important biological target assays.…”
Section: Introductionmentioning
confidence: 99%